Study of the efficiency of career dump trucks in difficult high-altitude conditions - Саменов, Галымжан; Karazhanov, Абдикарим; Zhamanbayev, Бауыржан (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
The features of operation of mine dump trucks in high-altitude conditions when transporting coal over a long distance are considered. The calculation of options for solving the problem of coal transportation was carried out and optimal options were proposed for the implementation of the established transportation plan. If you reconstruct all bridge structures, ensure constant maintenance, timely cleaning of road sections from snow, fill the road with special binding materials during the ice season, and conduct irrigation in the summer, then 1 million tons of coal per year can be technologically transported along this road.